Falso e interessi epigrafici. Un viaggio fra testi e immagini di epoca umanistico-rinascimentale - Caccia, Eleonora (Elephant & Castle, 2017)
So intensely rediscovered during the Renaissance, epigraphs are precious evidence to retrace the truth of the past from different points of view, such as the language, the social composition, the artistic taste of a people. But epigraphy is also deeply connected with the dimension of the “false”. This essay intends to analyse some aspects of the epigraphic false from naive wrong interpretations of the inscriptions to gorgeous imaginary drawings in the codices, from playful inventions – possibly created to make fun of the scholars – to deliberate deceitful works. Enriched with several images of the manuscripts, ancient prints, artefacts and monuments, the journey ends with a curious testimony hovering between truth and fiction, discovered in a Sixteenth-century book and, so far, unpublished.